THE EFFECT OF PROFITABILITY, LEVERAGE, AND CORPORATE GOVERNANCE ON TAX AVOIDANCE IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE AND MALAYSIA EXCHANGE FOR THE PERIOD 2018-2020 - Ineu Dewi Santika; Daeng M. Nazier (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The aims of this study to examine the effect of profitability, leverage, and corporate governance on tax avoidance in the period 2018-2020. The population in this study was mining companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange during the 2018-2020 period. The research sample was determined by using purposive sampling technique with predetermined criteria so that obtain 24 mining companies that meet the requirements with observations for 3 consecutive years resulting in a total of 72 samples. The indicator for measuring tax avoidance uses the Cash Effective Tax Rate (CETR). The data used in this study were obtained from secondary data in the form of annual financial reports sourced from www.idx.co.id and www.bursamalaysia.com. The data analysis technique used in this study is the multiple linear regression method. The results of this research show that the variables of profitability, leverage, and corporate governance have a simultaneous effect on tax avoidance. However, the variables of profitability, leverage, and corporate governance do not have partial significant effect on tax avoidance.